Is Depression and Suicidality a Matter of Sexual Orientation? An Empirical Investigation in Greece - Kaprinis, Stergios; Charalampakis, Anastasios (Archives of Clinical and Biomedical Research, 2022)
Background: This research is based on previous literature concerning mental health conditions in sexual minorities. Taking this background into consideration, here, the role of sexual orientation and sexual orientationrelated stress is examined. Aims: The research aims to examine the predictors of depression and suicidality, focusing primarily on the role of sexual identity and sexual orientation-related stress. Methods: A questionnaire was distributed to a sample of 112 participants, from which 64 of them belonged to the LGB community. Results: The results showed that sexual orientation differentiated the median and distribution of depression and suicidality levels, but its effect was insignificant when adjusted with other demographic variables in regressions. Gay-related stress seems to be associated with higher levels of depression. Conclusion: More research is needed to shed light on the risk factors of depression and suicide, especially for LGB participants. Finally, the role of gay-related stress needs to be validated by further studies as well.